Let's define the next variables:
x: the first odd integer
y: the next odd integer
Since they are consecutive:
x + 2 = y
The product of them is 195, then:
x*y = 195
Replacing the y from the first equation into the second one:
x*(x + 2) = 195
x*x + x*2 - 195 = 0
x² + 2x - 195 = 0
Solving with help of the quadratic formula:
![\begin{gathered} x_(1,2)=\frac{-b\pm\sqrt[]{b^2-4ac}}{2a} \\ x_(1,2)=\frac{-2\pm\sqrt[]{2^2-4\cdot1\cdot(-195)}}{2\cdot1} \\ x_(1,2)=\frac{-2\pm\sqrt[]{784}}{2} \\ x_1=(-2+28)/(2)=13 \\ x_2=(-2-28)/(2)=-15 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/u7fcizcvvxrtlshakusm5j3u4jfobev19i.png)
Given that we are only interested in positive integers, the solution x = -15 is discarded.
Therefore, the integers are 13 and 15
The sum of them is 13 + 15 = 28